THE COMPOSITION OF STRUCTURAL STEEL USED IN THE REPUBLIC OF KAZAKHSTAN AND THE RELATIONSHIP WITH HARDNESS CHARACTERISTICS - Kulbayev, Begman; Lapin, Vladimir; Shakhnovich, Alexandr; Shokbarov , Yeraly; Aldakhov , Yerken (GEOMATE Journal, 2024)
The Republic of Kazakhstan possesses significant plant capacities for producing constructional steel sheets for use in the construction industry. Since 2015, a new Eurocode-based regulatory framework in construction has been in effect. One of the primary challenges addressed has been ensuring compliance of local structural steel with the chemical composition requirements of the Eurocode. To address this, chemical composition determinations have been conducted for seven types of steel commonly utilized in construction. The content of the main components was compared with the specifications outlined in EN 10025. It has been determined that the chemical composition of the local structural steel fully aligns with the requirements of EN 10025. For the first time, correlation dependencies between Brinell numbers and components of the steel's chemical composition have been established. A linear correlation between the Brinell hardness factor and the percentages of carbon, manganese, and silicon has been identified. The correlation coefficient in this context ranges from 0.7 to 0.8, indicating a stable correlation relationship. This study provides an example of determining Brinell hardness based on the carbon or manganese content in steel samples. Additionally, utilizing the correlation dependence, the impact strength was determined. The findings of this research are expected to significantly improve the utilization of Kazakh structural steel in design and construction applications.